The GATT and Its Implications on the Philippine Economy - Commerce and Industry, Philippine Chamber of (Kasarinlan: Philippine Journal of Third World Studies; Vol 24 No 1-2 (2009): The Philippines in the WTO, 2011)
In this position paper, the Philippine Chamber of Commerce and Industry believes that General Agreement on Tariffs and Trade (GATT) member-countries definitely stand to benefit from the agreement resulting from the Uruguay Round of GATT negotiations. The Philippines, in particular, stands to profit from a) concessions given by developed or highly industrialized countries in the form of tariff reductions for many of its agricultural products and b) preferential treatment because of the treaty’s Most Favored Nation component. Whatever losses the Philippines may suffer because of the latest GATT treaty are minimal and short-term. Even tourism is projected to receive a boost from the new treaty. The paper seeks to show that GATT is a necessary step for the standardization and simplification of multilateral trade, allowing its members to fully reap the benefits of a system based on comparative advantage. GATT should also be viewed as an indication of the direction that world trade is headed towards in the near future. If the Philippines does not fully comply with GATT’s requirements or implement measures that will allow it to compete in a liberalized global economy, it will not only find itself immediately at odds with its trading partners, but it will also find itself incapable of internally reforming its economic structures in order to attain sustainability. In this age of international trade liberalization, it is no longer economically sound to stand apart from the rest of the world.
Keywords: Philippine Chamber of Commerce and Industry · GATT · Uruguay round · Most Favored Nation · multilateral trade · Philippines